Effect of pregnancy planning and fertility treatment on cognitive outcomes in children at ages 3 and 5: longitudinal cohort study. (26th July 2011) - Carson, C; Kelly, Y; Kurinczuk, J J; Sacker, A; Redshaw, M; Quigley, M A
Abstract : Objective To investigate how pregnancy planning, time to conception, and infertility treatment influence cognitive development at ages 3 and 5. Design Prospective population based cohort study. Setting Millennium Cohort Study in the United Kingdom. Participants 18 818 children recruited at 9 months and followed up at 3 and 5 years. 11 790 singletons with available data on pregnancy, cognitive outcomes, and confounders were included in analyses at age 3 and 12 136 at age 5. Exposure measures Mothers reported whether the pregnancy was planned, and their feelings when first pregnant; those in whom the pregnancy was planned provided time to conception, and details of any assisted reproductive technologies. The population was divided into "unplanned" (unplanned and unhappy), "mistimed" (unplanned but happy), "planned" (planned, time to conception <12 months), "subfertile" (planned, time to conception ≥12 months), "induced ovulation" (received clomiphene citrate), and "assisted reproduction" (in vitro fertilisation or intracytoplasmic sperm injection). The "planned" group was the comparison group in all analyses. Outcome measures Three components of the British Ability Scales (BAS II). Naming vocabulary assessed verbal ability at age 3; this test was repeated at age 5 with the picture similarities and pattern construction subscales, which measure non-verbal and spatial abilities. Results In unadjusted analyses, the scores on all scales in children from unplanned pregnancies were significantly lower than in those from planned pregnancies—for example, the difference in mean verbal ability score at age 3 was −4.8 (95% confidence interval −6.0 to −3.7; P<0.05), equivalent to an average delay of four months. After adjustment for sociodemographic factors these differences were attenuated: −0.3 (−1.3 to 0.7), equivalent to no delay. Children born after assisted reproduction performed consistently better in verbal ability tests (3.8 (−0.2 to 7.9) at age 3 and 3.5 (0.2 to 6.8) at age 5), which suggests that on average these children are three to four months ahead; this difference did not completely disappear with adjustment for confounders. Children born after infertility treatment had lower mean scores in non-verbal tests (−1.2 (−4.1 to 1.6) after assisted reproduction and −1.5 (−3.5 to 0.4) after induced ovulation) and in spatial ability tests (−2.7 (−6.9 to 1.6) after assisted reproduction), though the differences were not significant. Conclusions Pregnancy planning, subfertility, or assisted reproduction do not adversely affect children's cognitive development at age 3 or 5. The differences observed in the unadjusted analyses are almost entirely explained by marked inequalities in socioeconomic circumstances between the groups.